Geoinformation Monitoring оf Population Reproduction in Russia - V. O. Esikova (Наука. Инновации. Технологии)
Introduction. In the last decades of the XX–XXI centuries, the nature of population reproduction in Russia and its regions has changed. During the post-Soviet period, the country is undergoing a deep demographic crisis, depopulation processes have been actively developed. In this regard, geoinformation monitoring of population reproduction in Russia becomes relevant.Materials and research methods. Geoinformation monitoring of population reproduction was carried out at the level of Russia and regions using two components of reproduction: natural movement and migration of the population. The spatial data base «Population Reproduction in Russia» is organized to analyze the transformation of population reproduction. The following methods are used in the study: typological, geo-information, centrographic method, method of qualitative and quantitative background, methods of cartographic diagrams, ranges of values, method of movement of arrows.Research results and their discussion. Russia is characterized by a decrease in the population. On average, the population is declining by 66 thousand people a year. There are 4 periods according to the nature of population reproduction: 1990–2000, 2001– 2010, 2011–2017, 2018–2021. A typology of regions was carried out with the construction of cartographic material, and the transformation of population reproduction was analyzed with the identification of all-Russian and regional trends in the formation of the population of the post-Soviet period in Russia.Conclusions. The process of population reproduction is heterogeneous both in time and space. The territory of Russia is characterized by a diverse dynamics of natural and migration growth in the regions, the preservation of one type of population reproduction is characteristic of an extremely small number of regions. The reproduction of the population from 2011-2017 should be noted since the process is undergoing significant changes, in the regions of Russia there is a positive overall population growth associated with a reduction in the natural population decline and migration growth in the territory.